BLOCK CHAIN TECHNOLOGY AND ITS APPLICATIONS IN BUSINESS DECISIONS (INTERNATIONAL JOURNAL OF APPLIED SCIENCE & TECHNOLOGY, 2021)
Blockchain technology has the ability to alter our commercial environment and will have a significant impact over the next ages. It has the ability to change our perspectives of company processes and transform our society. Blockchain is essentially and public blockchain program that aims to provide visibility, data protection, and authenticity since it cannot be interfered with or created. The majority of mainstream Blockchain Technology studies have been focused on its usage for cryptocurrencies such as Bitcoin, with just a few studies looking at its use in other contexts or areas. Blockchain technology is much more than simply bitcoin; it has potential applications in administration, finance and economics, bookkeeping, and managed services, among others. As a result, the goal of this study is to examine and investigate the merits and drawbacks of Blockchain Technology for application potential.
Keywords: Blockchain; Cryptocurrency; Applications; Business decisions